2016
DOI: 10.1002/ajpa.22978
|View full text |Cite
|
Sign up to set email alerts
|

A bioarchaeological analysis of oral and physiological health on the south coast of New Guinea

Abstract: It is suggested that the causes for the variation in oral and physiological health were likely multifactorial and potentially associated with variables such as the ecological and geographical settings of the sites, cultural differences, infectious disease, differential fertility and, potentially, diet. This research provides previously unknown information about possible culturally-moderated practices that affected health in the past. Am J Phys Anthropol 160:414-426, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…There is an increasing trend in the field of using more refined age estimation techniques, such as Transition Analysis Boldsen, Milner, Konigsberg, & Wood, 2002), and we expect that the availability of data with better estimates of age in the future will be useful to correct the current limitation of this variable in the analyses of age-dependent markers (Knudson & Stojanowski, 2008). However, we chose to keep this threestage system because it represents a common scoring system used by many contemporary bioarchaeologists (e.g., Fontanals-Coll, Subira, Diaz-Zorita Bonilla, & Gibaja, 2017;Kinaston, Roberts, Buckley, & Oxenham, 2016;Marklein, Leahy, & Crews, 2016;Scott, Choi, Mookherjee, Hoppa, & Larcombe, 2016;Yaussy, DeWitte, & Redfern, 2016;Yonemoto, 2016;Zampetti, Mariotti, Radi, & Belcastro, 2016).…”
Section: Materials a Nd Methodsmentioning
confidence: 99%
“…There is an increasing trend in the field of using more refined age estimation techniques, such as Transition Analysis Boldsen, Milner, Konigsberg, & Wood, 2002), and we expect that the availability of data with better estimates of age in the future will be useful to correct the current limitation of this variable in the analyses of age-dependent markers (Knudson & Stojanowski, 2008). However, we chose to keep this threestage system because it represents a common scoring system used by many contemporary bioarchaeologists (e.g., Fontanals-Coll, Subira, Diaz-Zorita Bonilla, & Gibaja, 2017;Kinaston, Roberts, Buckley, & Oxenham, 2016;Marklein, Leahy, & Crews, 2016;Scott, Choi, Mookherjee, Hoppa, & Larcombe, 2016;Yaussy, DeWitte, & Redfern, 2016;Yonemoto, 2016;Zampetti, Mariotti, Radi, & Belcastro, 2016).…”
Section: Materials a Nd Methodsmentioning
confidence: 99%
“…Linear enamel hypoplasia (LEH) is formed when there is an interruption in the enamel matrix secretion during tooth development; it manifests as a horizontal linear depression around the dental enamel (Goodman and Rose 1990; Hillson 1996). This defect is usually caused by physiological stress events occurring during infancy, when dental crowns are still forming (Kinaston et al 2016). The presence of LEH was verified macroscopically according to the FIELD method (Brickley and McKinley 2004; Buikstra and Ubelaker 1994), which uses a 10× magnifying glass and a LED flashlight positioned perpendicularly to teeth occlusal surfaces.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have identified that within hierarchically ranked societies, selective distribution of resources determined by social position and status generates variations in physiological stress, which in turn impact upon the physical development and susceptibility to infectious and deficiency diseases of individuals within that society (Bennike, Lewis, Schutkowski, & Valentin, 2005;Goodman, Brooke-Thomas, Swedlund, & Armelagos, 1988;Goodman & Martin, 2002;Peck, 2013;Temple & Goodman, 2014). However, research is increasingly demonstrating multifaceted influences that stimulate the expression of biological and physiological stress upon the skeleton, including differential fertility (Kinaston, Roberts, Buckley, & Oxenham, 2016), epigenetic inertia (Klaus, 2014), social practices such as weaning (Ash, Francken, Pap, Tvrdý, Wahl, & Pinhasi 2016), social and economic change (King, Humphrey, & Hillson, 2005), and varying day-to-day physical activities experienced by different social, occupational, or gender groups (Robb et al, 2001).…”
Section: Introductionmentioning
confidence: 99%